2010
DOI: 10.1007/s10165-010-0354-y
|View full text |Cite
|
Sign up to set email alerts
|

Anti-ribosomal P protein antibody induces Th1 responses by enhancing the production of IL-12 in activated monocytes

Abstract: Autoantibodies to ribosomal P proteins (anti-P) are detected in 12-16% of patients with systemic lupus erythematosus (SLE), and have been found to be associated with some manifestations, including lupus psychosis, nephritis and hepatitis. We have recently disclosed that anti-P react with activated human peripheral blood monocytes, and enhance their production of tumor necrosis factor-α and interleukin (IL)-6. It is also possible that anti-P might regulate other monocyte functions, including the regulation of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
2

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
2
6
0
2
Order By: Relevance
“…Nonetheless, T H 1 effector cells and IFN-γ production within target tissue play an important role in organ damage in lupus, particularly in the onset and progression of glomerulonephritis (17). Indeed, autoantibodies against ribosomal P, which are associated with lupus nephritis, have been shown to induce IFN-γ production (18). …”
mentioning
confidence: 99%
“…Nonetheless, T H 1 effector cells and IFN-γ production within target tissue play an important role in organ damage in lupus, particularly in the onset and progression of glomerulonephritis (17). Indeed, autoantibodies against ribosomal P, which are associated with lupus nephritis, have been shown to induce IFN-γ production (18). …”
mentioning
confidence: 99%
“…Reinforcing this possibility, previous studies have demonstrated that ribosomal P0 proteins are expressed on the surface of hepatoma cells and anti‐rib P antibodies can penetrate into live hepatoma cells and cause cellular dysfunction . Moreover, anti‐rib P has the capacity to react with activated human peripheral blood monocytes and enhance the production of tumour necrosis factor‐α, interleukin‐6 and interleukin‐12, thus inducing a Th1 immune response . In AIH, the role of Th1 immune response is well established, as IFN‐γ secreted by Th1 cells is the main mediator of tissue damage in this disease .…”
Section: Discussionmentioning
confidence: 99%
“…In vitro , anti-P antibodies from patients with diffuse NPSLE can directly react with the surface of human peripheral blood monocytes, which results in TNF-α production [73]. Therefore, anti-P antibodies could be associated with auto antibody-mediating inflammation in the CNS through the mechanism of BBB rupture by monocyte-derived TNF-α with or without infiltration of activated macrophage into CNS [73]. Accordingly, anti-P antibodies might also activate the immune system, access the CNS, and directly damage neurons in SLE patients [48,73].…”
Section: Autoantibodies In Sle and The Induction Of Behavioral Abnormmentioning
confidence: 99%